Religious Minorities and Legal Protection: A Critical Review of Indonesia's Religious Freedom Laws (Indonesian Minority Justice Review, 2024)
This paper critically examines the legal protections for religious minorities in Indonesia, focusing on the effectiveness of religious freedom laws in safeguarding minority faiths. Indonesia, a majority Muslim country, officially recognizes six religions, but religious minorities, including Christians, Hindus, Buddhists, and indigenous belief systems, often face discrimination and legal challenges. The study reviews key legal frameworks such as the 1945 Constitution and the Law on Religious Harmony (2006), and assesses their ability to protect religious minorities from discrimination, violence, and marginalization. Through legal analysis and interviews with religious leaders and minority group representatives, the research reveals that while religious freedom is enshrined in law, in practice, many religious minorities struggle with bureaucratic hurdles, local regulations, and societal hostility. The paper also examines high-profile cases of religious intolerance and the role of local governments in either upholding or undermining religious freedoms. The findings suggest that while there are legal protections in place, they are often inadequately enforced, and religious minorities remain vulnerable to exclusion. The paper concludes by proposing reforms aimed at strengthening the legal framework for religious freedom, including more robust anti-discrimination laws and better enforcement mechanisms at the local level.